2003
DOI: 10.1021/ic030043r
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Sixth Axial Ligand in CS-Ligated Iron(II)octaethylporphyrinates:  Structural and Mössbauer Studies

Abstract: The effect of a sixth ligand in a series of low-spin thiocarbonyl-ligated iron(II)octaethylporphyrinates has been investigated. Six-coordinate complexes have been synthesized and characterized by Mössbauer and infrared spectroscopy and single-crystal X-ray structure determinations. The results are compared with the five-coordinate parent complex. The crystal structures of [Fe(OEP)(CS)(1-MeIm)] and [Fe(OEP)(CS)(Py)] are reported and discussed. The 1-methylimidazole and pyridine derivatives exhibit Fe-C(CS) bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 68 publications
1
19
1
Order By: Relevance
“…Similar differences are seen in carbonyl or thiocarbonyl complexes with pyridines or imidazoles trans to the CO [58,59,60] or CS. [61] The effect of differing trans bond distances is likely the difference that imidazoles are modest π-electron-donors compared to the modest π-accepting character of pyridine. [62,63] Clearly, one can expect that the cyanide and pyridine will compete for the same iron π density whereas the imidazole can π-donate and hence form a stronger bond.…”
Section: Discussionmentioning
confidence: 99%
“…Similar differences are seen in carbonyl or thiocarbonyl complexes with pyridines or imidazoles trans to the CO [58,59,60] or CS. [61] The effect of differing trans bond distances is likely the difference that imidazoles are modest π-electron-donors compared to the modest π-accepting character of pyridine. [62,63] Clearly, one can expect that the cyanide and pyridine will compete for the same iron π density whereas the imidazole can π-donate and hence form a stronger bond.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that certain characteristics, e.g., atomic/ionic radii [2], and bond length as well as hardness [2,7], of lanthanide compounds show irregular patterns, i.e., a smooth trend is not followed. Unfortunately, to the best of our knowledge, the influence of ligands on the periodic properties of organolanthanides is not noticed so far although ligand effect was found to affect the structure and activity of transition metal complexes [8,9]. It is also noteworthy here that density functional theory (DFT) calculations performed on certain lanthanide complexes [2,[10][11][12] show the significance of relativistic effects.…”
mentioning
confidence: 90%
“…The relatively large iron out of plane displacements (Δ 24 and Δ 4 ) and the longer Fe–C carbene distances of the two [Fe­(TFPP) (CPh 2 )] structures are also consistent with the steric effect of CPh 2 . The key structural parameters of the well-studied, low spin [Fe­(II) (Porph) (XY)] (XY = CO, CS and CN – ) are also given in Table . It is seen the Δ 24 (and Δ 4 ), and the (Fe–N p ) av distances of the carbene complexes are in the range of 0.17–0.30 and 1.96–1.99 Å.…”
mentioning
confidence: 99%